AIR SERBAT SEBAGAI SUMBER FITONUTRIEN TRADISIONAL MASYARAKAT MELAYU DI KOTA PONTIANAK - Hildawati Hildawati; Rere Pauztio Noso; Lutfiah Lira Irwanti; Delta Nabilla Maharani; Irwayuni Irwayuni (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2025)
Serbat is a spiced beverage embedded in the daily life of the Malay community in Pontianak and is culturally understood to possess various health benefits. This study aims to describe the structural composition of serbat recipes, the community’s health-related interpretations, and their relationship to phytonutrient content through the perspectives of Ethno-Nutrition and Medical Ethnobiology. Through observations and in-depth interviews with six key informants, the study identifies that serbat consists of core ingredients—cloves, cinnamon, and cardamom—and a set of variable ingredients such as pandan leaves, sappan wood, nutmeg, star anise, anise seeds, and rosella, which reflect domestic adaptation. Emically, serbat is understood to serve four primary health functions: warming the body, sustaining stamina, alleviating leg discomfort, and providing digestive comfort. These interpretations correspond with the bioactive properties of the spices, including eugenol and cinnamaldehyde that produce warming effects, polyphenols and flavonoids that support energy metabolism, brazilin and myristicin with anti-inflammatory activity, and gastroprotective compounds found in cardamom, pandan, and anise. These findings demonstrate that serbat constitutes a biocultural product that bridges culinary tradition, sensory experience, and phytochemical mechanisms, thereby illustrating the continuity of traditional nutritional knowledge within the context of modern health practices.